IMPROVING STUDENT ACTIVITIES AND LEARNING OUTCOMES IN CLASS III SDN 021 LADA USANG THROUGH LEARNING ASSOCIATION APPROACH USING LEARNING VIDEOS - Arni Delita (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2020)
This research is motivated by the teacher-centered learning activities and the low student learning outcomes. This research was expected to mprove student learning activities and outcomes. This research was a classroom action research on class III students of SDN 021 Lada Usang with 13 students. This research was conducted from September to October 2019. The instrument used in this study was the observation sheet of student activities and student learning outcomes tests. The results of this research showed that the activity of students in the first cycle of 61% with an active category increased in the second cycle to 83% which is included in the very active category. The average learning outcomes of students in the first cycle was 74.34 with a percentage of classical completeness while of 69%, in cycle II an increase of 80.38 with a classical completeness of 84% which was included in the excellent category. Based on the results of this study it can be concluded that the scientific approach with the help of instructional video media can improve student learning activities and outcomes.